A rare gigantic primary epithelial cyst of spleen in an adolescent boy - N., Kiran George; Balachandran, Gayatri; Mohan, L. N. (International Surgery Journal, 2017)
Cysts arising from spleen are a rare clinical entity, with their discovery usually being incidental. We present a case of the largest reported primary epithelial cyst of spleen. In present study a 16-year-old child presented with abdominal distension for 1 month associated with abdominal pain for 2 weeks. On examination, a mass was felt in the epigastrium, left hypochondrium and left flank, extending across from the right midclavicular line to the left midaxillary line, and extended inferiorly till 6cm caudal to umbilicus. CT abdomen revealed a unilocular cyst of 17x20x24cm arising from the spleen with a volume of 3700ml. Splenectomy was performed; intra-operatively there was a huge splenic cyst measuring 30x30x30cm. Histopathological examination was diagnostic of Primary congenital epithelial cyst of the spleen. Till date the largest congenital splenic cyst documented in literature is 20 cm × 13 cm × 21 cm, as reported by Valentina et al, in 2014. Present specimen bests this previous case considerably.